COMPARATIVE ANALYSIS OF PHRASEOLOGICAL UNITS WITH COLOR SEMANTICS IN THE GERMAN AND UZBEK LANGUAGES - Yulduz Ruzikulovna Juraeva (Modern American Journals, 2025)
This article presents a comparative analysis of phraseological units with color semantics in the German and Uzbek languages. The main aim of the study is to identify common and nationally specific features of color components in the phraseology of the two languages. The results of the analysis show that color-based phraseological units reflect cultural, historical, and mental characteristics inherent to the speakers of each language. The findings of the study may be applied in linguocultural studies, comparative linguistics, and the practice of teaching foreign languages.
Keywords: Phraseology, color semantics, comparative analysis, German language, Uzbek language, linguoculture.